2013
DOI: 10.1007/s00134-013-3049-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improvement in preoperative oral health on nosocomial pneumonia in a group of cardiac surgery patients: a single arm prospective intervention study

Abstract: PP rates were reduced using a simple and efficient protocol of dental care that improved oral hygiene in the preoperative period of cardiac surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 33 publications
2
51
1
5
Order By: Relevance
“…Real major advances will come from rapid PCR point-of-care techniques, but these results are not yet available. In 2014, Bos et al [44] published an article in the What's New in Intensive Care section on potential innovations that could improve early recognition of VAP. Those authors suggested that new techniques are promising in detecting airway colonization and pulmonary infection at the early phase.…”
Section: Ventilatory-acquired Pneumoniamentioning
confidence: 99%
“…Real major advances will come from rapid PCR point-of-care techniques, but these results are not yet available. In 2014, Bos et al [44] published an article in the What's New in Intensive Care section on potential innovations that could improve early recognition of VAP. Those authors suggested that new techniques are promising in detecting airway colonization and pulmonary infection at the early phase.…”
Section: Ventilatory-acquired Pneumoniamentioning
confidence: 99%
“…With regard to the preoperative environment, it is suggested that the use of a simple oral hygiene protocol can reduce postoperative pneumonia [13].…”
Section: Oral Carementioning
confidence: 99%
“…30 It remains uncertain, however, whether such an approach could reduce the rate of VAp in surgical patients. Bergan et al 31 tried to reduce the rate of postoperative pneumonia in cardiac surgery patients by implementing a care bundle focused on optimizing oral health before surgery. patients were taught how to brush teeth and tongue and how to clean their jugal and palatal membranes.…”
Section: Ventilation and Sedationmentioning
confidence: 99%